SISTEM PAKAR DIAGNOSA PENYAKIT LEUKOSIT MENGGUNAKAN METODE DEMPSTER-SHAFER (STUDI KASUS : RSU AL FUADI BINJAI) - Cindy Primadona Siahaan; Rusmin Saragih; Arnes Sembiring (Jurnal Manajamen Informatika Jayakarta, 2023)
In English, contains the main issues, problems, research objectives, methods / approaches and research Leukocytes are the largest blood cells, consisting of granulocytes and agranulocytes. Granulocytes (have granules) include neutrophils, eosinophils, and basophils. There are several problems that occur if there are abnormalities in blood cells that can cause problems for eosinophils, basophils, neutrophils, lymphocytes and monocytes. To find out the symptoms, the patient must see or have himself checked by a specialist in internal medicine. RSU Al Fuadi Binjai is one of the institutions that handles problems in patients with leukocyte disease. Internal medicine specialists are only able to make a diagnosis based on experience or the results of studies in the past that have occurred, but there are several obstacles in meeting a specialist doctor who treats leukocyte disease, including: long distance from the hospital, minimal costs, and lack of free time and others. Therefore, it is very necessary to have a system that can become information and alternative media for experts in diagnosing leukocyte disease, so that patients who have previous symptoms can get information and consultation more quickly through a system that has been created using the Dempster Shaper method, and get early action in knowing leukocyte disease through the symptoms experienced by the patient. The purpose of this study is to design and build a leukocyte disease diagnostic system using the Dempster Shafer method. Based on research conducted on selected symptoms, the most accurate diagnosis is monocyte disease with a confidence level of 0.9078 or 90.78% if used as a presentation.